Impact of Federal, State, and Local Housing Policies on Disparities in Cardiovascular Disease in Black/African American Men and Women: From Policy to Pathways to Biology - Sistrunk, Christopher; Tolbert, Nora; Sanchez-Pino, Maria Dulfary; Erhunmwunsee, Loretta; Wright, Nikita; Jones, Veronica; Hyslop, Terry; Miranda-Carboni, Gustavo; Dietze, Eric C.; Martinez, Ernest; George, Sophia; Ochoa, Augusto C.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Racist and discriminatory federal, state, and local housing policies significantly contribute to disparities in cardiovascular disease incidence and mortality for individuals that self-identify as Black or African American. Here we highlight three key housing policies – “redlining,” zoning, and the construction of highways – which have wrought a powerful, sustained, and destructive impact on cardiovascular health in Black/African American communities. Redlining and highway construction policies have restricted access to quality health care, increased exposure to carcinogens such as PM2.5, and increased exposure to extreme heat. At the root of these policy decisions are longstanding, toxic societal factors including racism, segregation, and discrimination, which also serve to perpetuate racial inequities in cardiovascular health. Here, we review these societal and structural factors and then link them with biological processes such as telomere shortening, allostatic load, oxidative stress, and tissue inflammation. Lastly, we focus on the impact of inflammation on the immune system and the molecular mechanisms by which the inflamed immune microenvironment promotes the formation of atherosclerotic plaques. We propose that racial residential segregation and discrimination increases tissue inflammation and cytokine production, resulting in dysregulated immune signaling, which promotes plaque formation and cardiovascular disease. This framework has the power to link structural racism not only to cardiovascular disease, but also to cancer.